A case study of using median as an alternative for signal controlled intersection. (2022) - Indhiradevi, P.; Saravanakumar, P.; Anandaraj, S.; Narendran, S.P.; Mohammed Anas, P.; Naveen Saran, S.R.; Nazir Ahamed, M.
Abstract: In major cities signalizing is more complicated problem at the intersection. The design of the signal is also toughest one especially four road meeting in the intersection. On that junction, the calm period of the vehicle is also high and it takes more time for crossing and moving of the vehicles. It leads to traffic congestion and accidents. This paper aims to design the medians over the signals injunction to control the traffic flow and ensure the continuous flow of the vehicles without waiting at the junction. Traffic flow rate at junctions may be controlled by considering the elements of transportation and social, political, economic considerations of the region. For this project, we analysed the traffic flow in the main junction where the movement of vehicle is higher and planned to remove the signals in the junction and construct the medians and pedestrian crossing bridge to control the traffic.